Inhibition of transfer of collagen-induced arthritis into SCID mice by ex vivo infection of spleen cells with retroviruses expressing soluble tumor necrosis factor receptor. - Chernajovsky, Y; Adams, G; Podhajcer, O; Mueller, G; Robbins, P; Feldmann, M (1995)
Collagen-induced arthritis can be transferred into severe combined immunodeficiency (SCID) mice by spleen cells from diseased DBA/1 mice. The development of arthritis in SCID animals can be prevented by infection ex vivo of DBA/1 spleen cells with retroviruses expressing the monomeric soluble human p75 tumor necrosis factor (TNF) receptor (TNF-R). In addition, a vector engineered to express a polycystronic mRNA with TNF-R and the herpes simplex virus thymidine kinase (HSVtk) gene, while producing low levels of TNF-R, had a limited effect which could be blocked by treating the animals with ganciclovir. A retroviral vector expressing the HSVtk gene alone had no effect on this arthritis transfer model with or without ganciclovir. Serum levels of TNF-R did not correlate with clinical signs, however, lower anti-collagen antibody levels corresponded with lack of clinical symptoms. These results indicate that local production of cytokine inhibitor is essential for therapeutic purposes while systemic levels may not be required.